Specific functions of BIG1 and BIG2 in endomembrane organization. - Frédéric Boal; David J Stephens (PLoS ONE)
Background Transport of molecules from one subcellular compartment to another involves the recruitment of cytosolic coat protein complexes to a donor membrane to concentrate cargo, deform the membrane and ultimately to form an independent carrier. Small-GTP-binding proteins of the Arf family are central to many membrane trafficking events. Arfs are activated by guanine nucleotide exchange factors (GEFs) which results in their recruitment to membranes and subsequent engagement with Arf-effectors, many of which are coat proteins. Among the human BFA-sensitive large Arf-GEFs, the function of the two closely related BIG1 and BIG2 is still not clear, and recent studies have raised the question of functional redundancy between the two proteins. Methodology/principal findings Here we have used small-interfering RNA on human cells and a combination of fixed and live-cell imaging to investigate the differential functions of BIG1 and BIG2 in endomembrane organization and function. Importantly, in this direct comparative study, we show discrete functions for BIG1 and BIG2. Our results show that depletion of BIG2 but not of BIG1 induces a tubulation of the recycling endosomal compartment, consistent with a specific role for BIG2 here. In contrast, suppression of BIG1 induces the formation of Golgi mini-stacks still polarized and functional in terms of cargo export. Conclusions A key finding from our work is that suppression of BIG1 expression results in a fragmentation of the Golgi apparatus. Our data indicate that the human BFA-sensitive large Arf-GEFs have non-redundant functions in cell organization and membrane trafficking. BIG1 is required to maintain the normal morphology of the Golgi; BIG2 is important for endosomal compartment integrity and cannot replace the function of BIG1 in Golgi organization.